Management of Slum Settlements based on Sustainable Development in the Deli Watershed of Medan City - Adang Aldhila; Hardi Warsono; Sri Suwitri; Retno Sunu Astuti (Budapest International Research and Critics University, 2021)
The population in urban areas continues to increase while the land owned is limited which results in slum settlements in urban areas. Slum settlements in Medan City often appear in areas where buildings should not be allowed, such as in watersheds. Deli River as a large river that divides Medan City, there are still many slum settlements in the watershed. Management of slum settlements based on sustainable development is needed to provide a long-term impact, especially for the preservation and restoration of the function of the Deli River. This study aims to analyze the management of slum settlements based on sustainable development indicators in achieving sustainable development, namely ecological sustainability, economic sustainability, socio-cultural sustainability, political sustainability, and defense and security sustainability. The research method used is descriptive qualitative. Sources of research data by collecting primary data through interviews and secondary data through documentation and observation studies. The management of slum settlements based on sustainable development in the Deli watershed is still not optimal in terms of ecological sustainability, economic sustainability, and defense and security sustainability. Meanwhile, socio-cultural sustainability and political sustainability are quite optimal. The government must manage slum settlements based on sustainable development through an approach with the community and provide viable housing alternatives so that people do not live in watershed areas.